2021
DOI: 10.1080/02640414.2021.1949189
|View full text |Cite
|
Sign up to set email alerts
|

Developing motor competency in youths: Perceptions and practices of strength and conditioning coaches

Abstract: Motor competency is integral to the long-term athletic development of youths. Strength and conditioning (S&C) coaches are recommended to deliver motor competency interventions, yet no studies have investigated their perceptions and practices for developing motor competency in youths. Sixty-seven male, and 4 female S&C coaches completed an initial and follow up questionnaire using a 5-point Likert scale, rating 1] the importance of developing competence, and 2] how frequently they developed competence across 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Using evidence-based resources alongside a framework to embed FMS may help overcome some of the barriers to implementation. 44 For example, this might include integrating FMS into warm-ups or skill-based practices, such as those previously published using the RAMPAGE framework by Till et al 45 Such assertion aligns with conclusions drawn by Burton et al 29 relating to maximising time to develop FMS in their work examining practice and perceptions of FMS in youth strength and conditioning coaches. There are good examples of evidence-based digital approaches such as the icoachkids project (icoachkids.org) and within teacher education and physical education which might offer a template that could be used with coaches.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Using evidence-based resources alongside a framework to embed FMS may help overcome some of the barriers to implementation. 44 For example, this might include integrating FMS into warm-ups or skill-based practices, such as those previously published using the RAMPAGE framework by Till et al 45 Such assertion aligns with conclusions drawn by Burton et al 29 relating to maximising time to develop FMS in their work examining practice and perceptions of FMS in youth strength and conditioning coaches. There are good examples of evidence-based digital approaches such as the icoachkids project (icoachkids.org) and within teacher education and physical education which might offer a template that could be used with coaches.…”
Section: Discussionmentioning
confidence: 70%
“…Lack of time has been previously reported as a barrier preventing coaches from implementing developmental activities in sports (e.g. soccer) 31,32 and prior work by Burton et al 29 has demonstrated that within youth strength and conditioning, those with greater session frequency (3-4 weekly sessions), could target 15-18% more motor competencies than those coaching 1-2 weekly sessions, irrespective of session duration. Moreover, while coaches did assess FMS, the measures that were employed were product-heavy (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the dynamic system theory perspective, the development of motor skills is based on the complex interaction between task, organism and environment [3]. The evolution of motor skills in any particular case depends on the difficulty of the tasks, the possibilities and opportunities of the environment and the physical and psychological properties of the child.…”
Section: Introductionmentioning
confidence: 99%
“…Despite development of motor competency at preschool age being critical for the overall development of individuals, information regarding the motor competency of preschool children with strabismus is limited. Motor competency is multidimensional, ranging from simple to combined to complex, which are all inter-related, and may be further divided into gross motor competency and fine motor competency in standardized assessments [ 17 , 18 ]. However, previous studies on children with strabismus tend to focus more on a single aspect, either gross motor competency [ 10 , 11 , 13 , 16 ], or fine motor competency [ 6 , 12 , 15 ], rather than complete motor competency [ 14 , 19 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%